تأثير أسلوب الصورة والصورة على مهارة كلام طلاب الفصل السابع ‏بمدرسة الهداية المتوسطة ميرو سيكاران لامونجان - Farid Qomaruddin; Khofifah (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2026)
The aim of this research is to determine the effect of visual and image-based techniques on the speaking skills of seventh-grade students at Al-Hidayah Middle School. The researcher employed a quantitative experimental approach. The sample consisted of 18 students from seventh grade "B" at Al-Hidayah Middle School. Data collection methods included a document-based test, divided into pre-test and post-test sections. SPSS 30 for Windows was used for data analysis, specifically the Normality Test, to test the research hypothesis. The results, based on the SPSS data, indicate that visual and image-based techniques have an effect on the speaking skills of seventh-grade students at Al-Hidayah Middle School. Based on the t-test using SPSS, the value of 9.602 (t-count) is greater than the value of 2.11% 5 sig (t-table), and there is a significant difference between the pre-test and post-test scores. Therefore, Ho is invalid and Ha is acceptable. This value indicates a significant effect. 2) The extent of the effect of the image and picture style on the speaking skills of seventh-grade students at Al-Hidayah Junior High School, Mero Sekaran Lamongan, is known from the results. The Cohens' D-estimate value is 2.263, which indicates a significant effect. Keywords: Picture and Picture Technique, Maharah Kalam, Arabic Language Education. ملخّص إن الأهداف من هذا البحث لمعرفة تأثير أسلوب الصورة والصورة على مهارة كلام طلاب الفصل السابع بمدرسة الهداية المتوسطة ومدى تأثير أسلوب الصورة والصورة على مهارة كلام طلاب الفصل السابع بمدرسة الهداية المتوسطة. استخدمت الباحثة المدخل الكمي بنوع التجريبي. أخذت الباحثة من الطلبة الفصل السابع "ب" بمدرسة الهداية المتوسطة. كان عدد عينة البحث 18طلبا. أما أسلوب البيانات المستخدم فهو الاختبار والوثائق. والاختبار ينقسم إلى قسمين الاختبار القبلي والاختبار البعدي. ولتحليل البيانات استخدمت الباحثة SPSS 30 for windows لاختبار تحليل المتطلبات الأساسية وهو الحالة الطبيعية للبيانات (Normality Test) و فرضية البحث. نتائج هذا البحث بناء على القيمة SPSS هي: 1) يوجد تأثير أسلوب الصورة والصورة على مهارة كلام طلاب الفصل السابع بمدرسة الهداية المتوسطة ميرو سيكاران لامونجان. بناء على اختبار t باستخدام SPSS هو أن قيمة 9،602 (t-count) أكبر من قيمة 2،11% 5 sig (t-table)، وهناك فرق معنوي بين درجات الاختبار القبلي والاختبار البعدي. وبالتالي، Hoمردود و Ha مقبول. فهذه القيمة تدل على تأثير كبير. 2) مدى تأثير أسلوب الصورة والصورة على مهارة كلام طلاب الفصل السابع بمدرسة الهداية المتوسطة ميرو سيكاران لامونجان من المعروف بنتائج قيمة point estimate cohens’D هو 2,263 التي تدل على فعال كبير. كلمات أساسية: أسلوب الصورة والصورة، مهارة الكلام، مدرسة الهداية المتوسطة الإسلامية سيكاران لامونجان.